Analysis of the Study of the Problem of School and Family Interaction in Preventing and Overcoming Bullying in the Digital Educational Environment - Fedorchenko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article is devoted to the pressing issue of school and family interaction in the prevention and overcoming of bullying in the digital educational environment. It emphasizes the development and implementation of modern forms and methods for preventing and addressing bullying in institutions of general secondary education within the digital space.A structured and substantiated technology of school-family interaction in combating bullying in the digital educational environment is presented. It includes: formation of awareness and beliefs (the reflexive-explicit method by I. Bekh), aimed at fostering students’ positive behavioural experiences; formation of aspirations and beliefs (narrative method – describing lived situations, using parables, creating video clips based on literary works that address bullying, violence, and moral values); method of personal representation (according to I. Bekh) – method of educational situations: creating web-posters, web-drawings, discussing moral foundations of personality development, analyzing video materials on bullying available online; formation of desirable behavioural experience – the method of social trials (safe communication in virtual space, cultivating a culture of Internet use in the daily lives of both parents and students); critical thinking method – identifying and debunking stereotypes in the digital environment; analyzing peer and media influence regarding bullying and cyberbullying; evaluating violent and non-violent solutions presented through the media.The methods of school and family interaction for the prevention and overcoming of bullying in the digital educational environment have been substantiated, described, and implemented. These include informational and educational methods, psychological, socio-pedagogical, administrative-organizational, and legal-organizational approaches.It has been proven that effective prevention and intervention against bullying in the digital educational environment must be conducted systematically and in an integrated manner, supported by all participants in the preventive and corrective process: students, teachers, parents, school administration, social services, and juvenile prevention authorities.The practical significance of the article lies in the fact that its materials can be used to organize educational and preventive work in general secondary education institutions and extracurricular education institutions, as well as by researchers, postgraduate students, and university students.